The Concept of Ᾱsana in Classical Yoga - Swain, Dinesh Prasad; Shree, Prativa (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 12 No 1 (2020): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
Yoga develops a healthy body and mind. It unlocks the petals of higher consciousness and leads the man beyond the horizon of limitations. Changing our whole being and even the attitude towards our life itself it expands our consciousness to the new possibilities. It aims at enabling us to know our own self with an integrated approach. Building a complete personality, a suitable vessel can be prepared to receive the influx of higher consciousness. Regular and intense practice of different yogic techniques are intended to develop the physical and mental transformation. Ᾱsana plays an important role to strengthen the muscles, joints, ligaments and tendons of the body. Regular practice of āsana maintains the physical body in an optimum condition and promotes health. The dormant energy potential is released and experienced with the increased confidence in each and every stage of life. One cultivates awareness, relaxation, concentration and meditation. There is development of the good physical health by stretching, massaging and stimulating the prāṇic channels and internal organs. The muscles and bones become strong, capacity to absorb oxygen increases with the ability to meet the physical demands during any situation in the day to day life. Sri Aurobindo has said, ‘The cup has to be left clean and empty for the divine liquor to be poured into it’. Regular practice of āsana provides a suitable foundation to explore the body and mind for the spiritual awareness.